Healing of iatrogenic double-barrel left main coronary artery dissection extending to the left anterior descending artery - Tokumasu, Yoshinori (J Cardiol Cases, 2021)
Iatrogenic left main coronary artery (LMCA) dissection is a complication inadvertently caused by the interventional cardiologist and can have significant consequences. A 38-year-old man presented to hospital with non-ST-elevation myocardial infarction. Coronary angiography (CAG) revealed an obstructed proximal left circumflex artery (LCx) that was successfully treated with revascularization using a drug-eluting stent (DES). However, CAG after recanalization of the LCx demonstrated a spiral dissection of the left coronary artery from the mid-LMCA to the left anterior descending (LAD) artery and LCx. The dissection was classified as National Heart, Lung and Blood Institute type D in LAD and type F in LCx. Immediate exclusion stenting of the dissection flap by another DES and thrombolysis in myocardial infarction 3 flow were achieved in the LAD and LCx. The patient achieved hemodynamic stability with improvement in symptoms, despite residual dissection in the LAD. We, therefore, preferred careful observation over revascularization. The false lumen remained visible with a double-barrel appearance in the LAD on 6-month follow-up CAG, which disappeared at the 2-year follow-up. We report a rare case of a large double-barrel dissection that spontaneously occluded over time without any aggressive interventions. <Learning objective: Iatrogenic left main coronary artery (LMCA) dissection is a rare but potentially life-threatening complication, with the associated risk of serious outcomes. Immediately after suffering a LMCA dissection, treatment strategies (conservative therapy, percutaneous coronary intervention, or coronary bypass grafting etc.) should be determined according to patient's symptoms and hemodynamic status. However, treatment strategies for chronic LMCA dissection are uncertain. Our case indicates that conservative therapy appears to be a potential option for the treatment of chronic asymptomatic and hemodynamically stable LMCA dissection.>